MENINGKATKAN PENGUASAAN KOSAKATA SISWA MELALUI PERMAINAN HYPONIM - Patahuddin, Patahuddin; Syawal, Syawal; Namrullah, Zulwahyuni (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research was based on students’ problems regarding the students’ vocabulary mastery in English teaching. Where the mean score was categorized as fair classification. Most of the students were not active in learning English language and also hard to understand learning material. Consequently, the students’ vocabulary mastery was low. The objective was to find out wheter the use of hyponymy game able to improve the vocabulay mastery of the students. The researcher applied quasi-experimental method, with two-group pre-test post-test design. The test form was vocabulary test that related to describtive text which consisted of 25 items. The samples was chosen by using random sampling technique which consisted of 60 students of the Tenth Grade Students of SMK Negeri 3 Parepare. Where X.TKJ.1 as experimental class and X.Multimedia.1 as control class. The result of the data analysis showed that the students’ vocabulary mastery improved significantly. It was proved by the mean score of pre-test was 55.86 and the post-test was 81.57. The mean score of the students in post-test was higer than Kriteria Ketuntasan Minimal (71) in SMK Negeri 3 Parepare. After analyzing the data by using SPSS 21, the result of probability value in post-test was (0.00) it was lower than significance value (α) = (0.05). Those indicated that H0 was rejected and H1 was accepted. It means that the students’ vocabulary mastery where taught by hyponymy game was effective to improve the vocabulary mastery of Tenth Garade Students at SMK Negeri 3 Parepare of academic year 2016/2017.